Acrobatic control of a pendubot. - Wei Li (IEEE Transactions on fuzzy systems)
This paper presents acrobatic control of an underactuated two-link robot called the pendubot. To achieve acrobatic control for the pendubot, we design a fuzzy controller for keeping first link swinging periodically while the second link maintains standing vertically. To facilitate the controller design, we represent the pendubot dynamics with a Takagi-Sugeno fuzzy model. We derive a linear matrix inequality (LMI) design condition to realize the acrobatic behavior. To accomplish the numerical feasibility design, we need to select carefully reference fuzzy model dynamics by taking into account some constraints. After selecting reference fuzzy model dynamics, an acrobatic controller is designed by solving the LMI condition. Simulation results show the utility of the proposed acrobatic control.